Design and Temperature Field Simulation of Mine Locomotive Brake and Test - Zhou Kun; Wang Jiqiang; Dong Mengshi (Jixie chuandong)
In order to realize the fast braking of motor vehicle at high speed and high load,the working principle of the existing braking system of mine electric locomotive and the problems in the process of braking are analyzed. The braking system of 6 tons of mine electric locomotive is designed,by using a caliper disc brake,and the main components structure sizes of brake disc,brake and drive mechanism are analyzed and calculated,according to the structure design of the brake and the calculated size,the simulation analysis of temperature field of the motor vehicle braking process is carried out by using the finite element simulation software.The temperature distribution cloud and the temperature distribution variation and the maximum temperature in the braking process of brake disc under the different adhesion coefficient are obtained. The simulation results meet the provisions of the motor vehicle industry brake temperature requirements. Finally,the designed electric locomotive is tested and analyzed,the synthetic results of simulation and test reveal the rationality of the brake design.